PKM PERSONAL & FAMILY FINANCE, LANGKAH MENUJU MASA DEPAN AMAN - Pangestu, Juan Carlos; Wijaya, Adinda Patricia (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
Many people are trapped in illegal online loans due to low financial literacy. To overcome this, the service team held a seminar on personal and family financial management with PT Artisan Kuliner Group on January 13, 2025. The seminar was entitled Personal & Family Finance: steps towards a secure future with PT Artisan Kuliner Group. The implementation was carried out in the UBM Seminar Room (TUSR), 7th floor of Bunda Mulia University and has been going well. The material discussed how to manage personal and family finances properly so that it is not only limited to controlling expenses or preparing a budget. but also includes long-term financial planning, such as preparing education funds, investments, and insurance protection.